2018
DOI: 10.1002/jlb.2ma1217-509r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chimeric chemokine as a specific ligand for ACKR3

Abstract: and CXCL11 bind to the canonical receptors CXCR4 and CXCR3, respectively. Here, we present the engineering of a chemokine-like chimera, which selectively binds to ACKR3. The addition of a ybbR13 tag at the C-terminus allows site specific enzymatic labeling with a plethora of fluorescent dyes. The chimera is composed of the N-terminus of CXCL11 and the main body and C-terminus of CXCL12 and selectively interacts with ACKR3 with high affinity, while not interfering with binding of CXCL11 and CXCL12 to their cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…mCCL20yAF 647 (15 µl, 30 nM in PBS) was injected into the food pad of wild‐type C57BL/6 mice, CCR6 ko C57BL/6 mice, 41 kindly provided by Sergio Lira, or heterozygous (ACKR4 GFP/wt ) and homozygous (ACKR4 GFP/GFP ) ACKR4‐EGFP knock‐in reporter mice 42 . After 15 min animals were sacrificed, the draining popliteal lymph node removed and fixed with formaldehyde by placing the specimens in 4% paraformaldehyde for 5 h. Vibratome sections were prepared as described 30 and stained with anti‐podoplanin‐PE (clone eBio8.1.1; eBioscience, San Diego, CA, United States) and anti‐B220‐biotin (clone RA3‐6B2; BD PharMingen, Allschwil, Switzerland)/streptavidin pacific blue (Thermo Fischer Scientific). Mice were treated in accordance with guidelines of the Swiss Federal Veterinary Office and experiments were approved by the Dipartimento della Sanità e Socialità.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mCCL20yAF 647 (15 µl, 30 nM in PBS) was injected into the food pad of wild‐type C57BL/6 mice, CCR6 ko C57BL/6 mice, 41 kindly provided by Sergio Lira, or heterozygous (ACKR4 GFP/wt ) and homozygous (ACKR4 GFP/GFP ) ACKR4‐EGFP knock‐in reporter mice 42 . After 15 min animals were sacrificed, the draining popliteal lymph node removed and fixed with formaldehyde by placing the specimens in 4% paraformaldehyde for 5 h. Vibratome sections were prepared as described 30 and stained with anti‐podoplanin‐PE (clone eBio8.1.1; eBioscience, San Diego, CA, United States) and anti‐B220‐biotin (clone RA3‐6B2; BD PharMingen, Allschwil, Switzerland)/streptavidin pacific blue (Thermo Fischer Scientific). Mice were treated in accordance with guidelines of the Swiss Federal Veterinary Office and experiments were approved by the Dipartimento della Sanità e Socialità.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we identify that ACKR4 is a specific scavenger for CCL20. Moreover and in accordance with the chimeric chemokine CXCL11_12, 30 we engineered a (fluorescent) chimeric chemokine consisting of the N‐terminus of CCL25 and the body of CCL19, that interacts with and is taken‐up by ACKR4.…”
Section: Introductionmentioning
confidence: 99%
“…A chemokine-like chimera, named CXCL11_12, has been reported as a high-affinity ACKR3-selective ligand. The structure of the engineered chimera consists of the N-terminus of CXCL12 and the main body and C-terminus of CXCL11, and the study showed the internalization of CXCL11_12 by mouse ACKR3, making the chimera a useful tool to study ACKR3 (Puddinu et al, 2017;Ameti et al, 2018).…”
Section: Chemokine and Peptide Binding To Cxcr4 And Ackr3mentioning
confidence: 99%
“…In addition, FC313, a cyclic pentapeptide ligand for CXCR7, which is modified at the I-Pro position with a bulky hydrophobic side chain, exhibited an improved bioactivity toward CXCR7 ( Sekiguchi et al, 2018 ). Most recently, Ameti et al (2018) reported a chimeric chemokine, which selectively binds to CXCR7. This chimera is composed of the N-terminus of CXCL11 and the main body and C-terminus of CXCL12 and selectively interacts with CXCR7 with high affinity, while not interfering with binding of CXCL11 and CXCL12 to their cognate receptors ( Ameti et al, 2018 ).…”
Section: Pharmacological Ligands Of Cxcr7mentioning
confidence: 99%
“…Most recently, Ameti et al (2018) reported a chimeric chemokine, which selectively binds to CXCR7. This chimera is composed of the N-terminus of CXCL11 and the main body and C-terminus of CXCL12 and selectively interacts with CXCR7 with high affinity, while not interfering with binding of CXCL11 and CXCL12 to their cognate receptors ( Ameti et al, 2018 ). We believe that all these newly generated ligands will be valuable pharmacologic tools for the study of CXCR7.…”
Section: Pharmacological Ligands Of Cxcr7mentioning
confidence: 99%